A new infinite solid solution strategy to design eutectic high entropy alloys with B2 and BCC structure. (1st July 2021) - Ye, Xicong; Xiong, Jinyan; Wu, Xin; Liu, Chang; Xu, Dong; Zhang, Wen; Fang, Dong; Li, Bo
Abstract: Eutectic highentropy alloys (EHEAs) have attracted wide attention in the metallic materials community because of its excellent castability, fine and controllable microstructure. However, the design method for eutectic EHEAs is still a challenge. In present work, a new infinite solid solution strategy was proposed to design EHEAs. Using this strategy, a series of EHEAs composed of ordered body centeredcubic (B2) and bodycentered cubic (BCC) phases were successfully developed with nano-structured precipitated phase. Some of the designed alloys in the current work have exhibited excellent compressive mechanical properties. Graphical abstract: Image, graphical abstract